Cinematic han and the Historical Film: South Korean Cinema and the Representation Of Korea’s Geopolitical Conflict in the Twentieth Century - McMahon, Niall Edward Peter (Curtin University, 2018)
A permanent Korean cultural aesthetic can be identified within South Korean historical cinema. By utilising a textual, historical and theoretical analysis methodology, this thesis examines South Korean films that depict Korean geopolitical conflict in the twentieth century to argue that this aesthetic, referred to as cinematic han, produces historical knowledge through the creation of symbolic links between the cinematic text and the context of its production.